2005
DOI: 10.1002/chir.20124
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective pharmacokinetics of RS‐8359, a selective and reversible MAO‐A inhibitor, by species‐dependent drug‐metabolizing enzymes

Abstract: RS-8359, (+/-)-4-(4-cyanoanilino)-5,6-dihydro-7-hydroxy-7H-cyclopenta[d]pyrimidine selectively and reversibly inhibits monoamine oxidase A (MAO-A). After oral administration of rac-RS-8359 to rats, mice, dogs, monkeys, and humans, plasma concentrations of the (R)-enantiomer were greatly higher than were those of the (S)-enantiomer in all species studied. The AUC((R)) to AUC((S)) ratios were 2.6 in rats, 3.8 in mice, 31 in dogs, and 238 in monkeys, and the (S)-enantiomer was almost negligible in human plasma. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

8
1

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 20 publications
(8 reference statements)
6
33
0
Order By: Relevance
“…Similar to those reports, we observed remarkable species differences, rat strain differences, and polymorphism-based individual differences in Donryu strain rat in the AO-catalyzed 2-oxidation activity of the (S)-enantiomer of RS-8359, [(Ϯ)-4-(4-cyanoanilino)-5,6-dihydro-7-hydroxy-7H-cyclopenta[d]-pyrimidine]. [14][15][16][17][18] The compound is a reversible and selective monoamine oxidase (MAO)-A inhibitor 19,20) and has been developed as an anti-depressant. 21,22) As to species differences, monkeys showed the highest activity followed by humans.…”
supporting
confidence: 89%
“…Similar to those reports, we observed remarkable species differences, rat strain differences, and polymorphism-based individual differences in Donryu strain rat in the AO-catalyzed 2-oxidation activity of the (S)-enantiomer of RS-8359, [(Ϯ)-4-(4-cyanoanilino)-5,6-dihydro-7-hydroxy-7H-cyclopenta[d]-pyrimidine]. [14][15][16][17][18] The compound is a reversible and selective monoamine oxidase (MAO)-A inhibitor 19,20) and has been developed as an anti-depressant. 21,22) As to species differences, monkeys showed the highest activity followed by humans.…”
supporting
confidence: 89%
“…18,19) The main metabolic pathway of the compound is the AO-catalyzed 2-oxidation on the pyrimidine ring of the molecule. Similar to many reports on AO, we observed a remarkable species differences, [20][21][22] a large strain difference in rat, 23) and an individual difference in Donryu strain rat 24) in the 2-oxidation activity. Further, we reported that a minor 130 kDa subunit in addition to a 150 kDa subunit was observed in the sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE)/Western blot analysis of monkey and human AO but not in rat AO.…”
Section: )supporting
confidence: 90%
“…All of these major metabolic events proceed with high enantioselectivity for the (S)-enantiomer that leads to more rapid disappearance of the (S)-enantiomer from plasma in every animal species. In particular, monkeys and humans have an extremely high aldehyde oxidase activity that results in an area under the curve AUC(R)/AUC(S) ratio of 238 in monkeys and a nearly negligible (S)-enantiomer in human plasma (Takasaki et al, 2005). There were no large variations in the in vitro 2-oxidation activity of RS-8359 using five human liver cytosol samples.…”
mentioning
confidence: 87%
“…One of the major metabolic pathways of RS-8359 is the 2-oxidation catalyzed by aldehyde oxidase (Iwabuchi et al, 1998;Takasaki et al, 2005). During the study of rat strain differences in the activity, we were aware of the individual variations in Donryu rats and carefully investigated the phenomenon from the perspective of molecular biology.…”
Section: Discussionmentioning
confidence: 99%